Citation analysis of academic literature on terrorism and social media in Indonesia - Ahsani Taqwim Aminuddin; Nurul Hasfi (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2024)
This research aims to evaluate the trends in publications regarding terrorism and social media in Indonesia in 2010 to 2023. The data is categorized by publication year, research topics, and fields of study. Researchers also calculated the citations received by each publication By using citation analysis, the study seeks to uncover patterns of scholarly attention, identify the most cited works, and determine the degree to which Indonesian research is integrated into the global discourse on terrorism and digital media. This research is necessary because of limited bibliometric assessment of how this field has grown and how influential it has been. The research findings indicate that publication trends peaked in 2021 in several topics such as radicalization/propaganda, counter radicalism/deradicalization, and religious moderation. The fields of Islamic studies and Communication studies were the most prolific in publishing studies on this subject. Of the 165 articles analyzed, only 15 articles received more than 10 citations in the broader terrorism research. On average, social media and terrorism research were cited only six times per publication in the broader terrorism literature. These suggest a lack of integration with the broader terrorism literature.